Effect of high volume fly ash on performance of grout and masonry cement mortar - Balakrishnan, Balamohan (2020)
Grout and mortar often selected for building repair and restoration works. However, these materials are also deteriorating and failed similarly as per the parent concrete or masonry structure due to environmental exposure, electrochemical reactions and mechanical loading. Previous studies and the available literature indicate that the failure of such repair material is mainly due to improper selection of material without knowing the material’s ability in order to improve the repair grout and masonry cement mortar is currently lacking. To address this, high volume fly ash (HVFA) in repair grout and masonry cement mortar is introduced. HVFA is selected as fly ash (FA) waste is still abundance and its unique spherical shape and pozzolanic property is suitable for this study. This research is first carried out by investigating the characteristics of the binders using X-ray Fluorescence Spectrometry (XRF), Scanning Electron Microscope (SEM) and X-Ray Diffraction (XRD). The performance evaluation of grout and mortar has been accomplished with specimens where Ordinary Portland Cement (OPC) and masonry cement (MC) is replaced by Class F FA up to 50%. The grout and mortar were subjected to workability test such as flow, viscosity and spread followed by mechanical properties such as compressive strength, bond strength and flexural strength. Durability of the material is finally evaluated by exposing them to aggressive substances such as acid, chloride and sulphate, and high temperature up to 1000 °C. HVFA results an excellent grout flow time with a reduction over 30% in flow time and maintained a fluid Bingham behaviour over 1 hour. Meanwhile, the mortar has an increment of 15% in spread. The compressive strength, flexural and splitting tensile shows that grout with 40% FA is close to the control value, while 50% FA grout is slightly lower at the end of 360 days. Opposite result is found with masonry cement mortar where HVFA exceeded control at 90 days. HVFA grout experienced approximately 50% lower amount of autogenous shrinkage and time to crack in drying shrinkage evaluation. The porosity of the HVFA grout is reducing with inclusion of FA at 360 days. While the mortar being air-entrained material, slightly affected by fly ash properties that results in additional water absorption. The HVFA’s pozzolanic, filler and dilution effect has contributed to remarkable performance against aggressive substances and condition for both materials. Grout being loaded with cement has 40% to 80% higher resistance to the chemical substances as compared to control, while mortar is the range of 80% to 100%. Test result on temperature rise shows HVFA able to reduce over 20 °C in peak temperature. Additionally, the thermal insulation behaviour of HVFA grout indicates slower response to heating by having additional 20 hours in time to reach 100 °C. The comparison between grout and masonry mortar shows good similarity, particularly in chemical resistance. Conclusively, the performance of HVFA in grout and masonry cement mortar has found to be satisfactory and can be used for concrete and masonry repair with increased durability. Both materials can be expected to compliment a sustaining building repair and restoration work.